2016
DOI: 10.1007/s00270-016-1545-5
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Ultrasound-Guided Carpal Tunnel Release: Study Upon Clinical Efficacy and Safety

Abstract: ObjectivesTo evaluate the feasibility and 6 months clinical result of sectioning of the transverse carpal ligament (TCL) and median nerve decompression after ultra-minimally invasive, ultrasound-guided percutaneous carpal tunnel release (PCTR) surgery.MethodsConsecutive patients with carpal tunnel syndrome were enrolled in this descriptive, open-label study. The procedure was performed in the interventional radiology room. Magnetic resonance imaging was performed at baseline and 1 month. The Boston Carpal Tunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 24 publications
2
70
0
1
Order By: Relevance
“…The primary finding of this study was that US‐guided CTR resulted in significant reductions in the US‐measured proximal median nerve CSA within 6 to 10 weeks after clinically successful US‐guided CTR. To our knowledge, this investigation was the largest to date describing postoperative changes in the proximal median nerve CSA after US‐guided CTR and supports previously published literature indicating that US‐guided CTR can result in both clinical and structural improvement in patients with CTS …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The primary finding of this study was that US‐guided CTR resulted in significant reductions in the US‐measured proximal median nerve CSA within 6 to 10 weeks after clinically successful US‐guided CTR. To our knowledge, this investigation was the largest to date describing postoperative changes in the proximal median nerve CSA after US‐guided CTR and supports previously published literature indicating that US‐guided CTR can result in both clinical and structural improvement in patients with CTS …”
Section: Discussionsupporting
confidence: 90%
“…Although most CTRs in the United States have been traditionally performed by using open or endoscopic approaches, advances in US technology have promoted the development of US‐guided techniques to transect the TCL (ie, US‐guided CTR). To date, more than 640 cases of US‐guided CTR have been reported in the peer‐reviewed literature, with a clinical success rate of greater than 95%, no major complications, and in some studies, superior early outcomes compared to traditional open CTR . However, only 3 previous publications evaluated the median nerve after US‐guided CTR.…”
mentioning
confidence: 99%
“…The aforementioned case illustrates the ability of US to confirm and monitor sonographic changes after USCTR, including improvement in median nerve CSA, TCL transection, and median nerve palmar displacement. Although Petrover et al [12] used magnetic resonance imaging at 1 month to document TCL transection and palmar displacement of the median nerve after USCTR, no previous reports have documented sonographic findings after USCTR. McShane et al [14] reported a reduction in median nerve CSA after USG needle release/fenestration of the TCL, but their technique did not completely transect the TCL.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ECTR, one advantage of USCTR is to reduce procedural morbidity and therefore promote a faster recovery However, USCTR provides a larger field of view than ECTR and allows the operator to transect the TCL while visualizing both the ligament and regional neurovascular structures in real time . Currently, more than 640 cases of USCTR have been reported in the peer‐reviewed literature without neurovascular injury and with satisfactory outcomes in greater than 95% of patients . In addition, a recently published prospective randomized trial comparing USCTR to mOCTR reported that USCTR was safe and resulted in statistically and clinically significantly faster recovery than the mini‐open technique …”
mentioning
confidence: 99%
“…7,9 Similarly, ECTR was developed to be less invasive than open CTR and transects the TCL through a single 1.0-to 1.5-cm distal forearm incision or both a 1.0-to 1.5-cm distal forearm incision and a 1.0-to 1.5-cm palmar incision, depending on the technique. 10 Nakamichi and Tachibana 11 first published on USCTR in 1997, and there has been increased interest in USCTR during the past 10 years, as evidenced by the number of peer-reviewed publications reporting cadaveric [12][13][14][15] and clinical 8,11,[16][17][18][19][20][21] results using various techniques. Similar to ECTR, one advantage of USCTR is to reduce procedural morbidity and therefore promote a faster recovery 8,21,22 However, USCTR provides a larger field of view than ECTR and allows the operator to transect the TCL while visualizing both the ligament and regional neurovascular structures in real time.…”
mentioning
confidence: 99%